Impacts of Pervasive Climate Change and Extreme Events on Rocky Intertidal Communities: Evidence From Long-Term Data - Mieszkowska, Nova; Burrows, Michael T.; Hawkins, Stephen J.; Sugden, Heather (Frontiers in Marine Science, 2021)
Annual surveys of the abundance of intertidal species have been conducted at up to 100 rocky intertidal time-series sites around the UK coastline since 2002 under the MarClim project. The data provide a unique opportunity to investigate the impacts of both pervasive climate change and extreme events on intertidal species. After the extreme storm events in the 2013/14 winter season and the record heatwaves in the summers of 2018 and 2020, MarClim surveys recorded physical and biological changes to rocky shore species. Subsequent surveys reassessed the abundance of species that resisted storm damage, species that returned after the extreme storm events, and species that opportunistically occupied vacant habitat after storm-induced species loss. In addition, biannual surveys documenting assemblage recovery were carried out in the spring and winter of each year from 2014 to 2020 at three MarClim sites in north Cornwall which experienced different types of abiotic and biotic impacts. Impacts of heatwaves and cold spells on the abundance of species were determined by regression on frequencies of event per year. Winter heatwaves tended to have a greater negative effect on cold-affinity species than on warm-affinity species, whereas summer heatwaves showed little overall impact on any species. Neither winter nor summer extreme cold spells showed any significant effect on species abundances. No abrupt shift was recorded after the 2013/14 storms. Whilst a short-term change in some species was recorded in quadrat surveys, the biological assemblage returned to the long-term composition within two years. The heatwave events caused sublethal heat damage in macroalgae, with mortality-induced reductions in the abundance of only a few invertebrate species, recorded in Scotland and southwest England. MarClim and storm-damage surveys indicate that there have been no sustained impacts from either extreme thermal or storm events across the rocky intertidal communities, and biodiversity has not been significantly altered as a result. The abundance and distributions of rocky intertidal species and communities around the UK are being driven by longer-term, large scale, pervasive change in environmental conditions, with a gradual shift towards dominance of lusitanian species from the early 2000s in responses to warming of the marine climate.